2013
DOI: 10.1093/mutage/ges080
|View full text |Cite
|
Sign up to set email alerts
|

T-cell-specific deletion of Mof blocks their differentiation and results in genomic instability in mice

Abstract: Ataxia telangiectasia patients develop lymphoid malignancies of both B-and T-cell origin. Similarly, ataxia telangiectasia mutated (Atm)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Purkinje cell-specific deletion of mouse MOF causes loss of these cells (Kumar et al, 2011). Ablation of MOF specifically in mouse T cells leads to defective cell differentiation and reduces T cell number and thymus size (Gupta et al, 2013). In mouse podocytes, MOF is required for cell-cycle progression in proliferating cells but is dispensable for terminally differentiated, postmitotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Purkinje cell-specific deletion of mouse MOF causes loss of these cells (Kumar et al, 2011). Ablation of MOF specifically in mouse T cells leads to defective cell differentiation and reduces T cell number and thymus size (Gupta et al, 2013). In mouse podocytes, MOF is required for cell-cycle progression in proliferating cells but is dispensable for terminally differentiated, postmitotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another laboratory also independently reported that Mof is essential for the progression of embryonic development past the blastocyst stage and is also required for normal chromatin architecture (85). In subsequent studies, histone acetyltransferase MOF was found to be a key regulator of the embryonic stem cell core transcriptional network and for the survival of post-mitotic Purkinje or T-cells (80, 81). Embryonic stem cells with Mof deletion lose characteristic morphology, alkaline phosphate staining, and differentiation potential.…”
Section: Dna Damage Responsementioning
confidence: 99%
“…Although a high level of H4K16ac is observed in GV stage oocyte , whether it is necessary for oogenesis is unknown. K (lysine) acetyltransferase 8 (KAT8, also known as MOF or MYST1) is a highly conserved MYST family member specifically responsible for H4K16 acetylation (Gupta et al, 2013). KAT8 contains a chromodomain for DNA binding and a C-terminal HAT domain for histone acetylation (Su et al, 2016).…”
Section: Introductionmentioning
confidence: 99%